Identification of Potentially Effective Antisense Oligodeoxyribonucleotide (ODN) Sequences for Inhibiting Plasminogen Activator Inhibitor-2 (PAI-2) Production by Monocytes - Humphries, Julia; Burnand, Kevin G.; Cunningham, Philip; Brock, Adrian; Westwood, Nigel; Smith, Alberto (Thrombosis and Haemostasis, 2002)
Monocyte fibrinolytic activity may influence thrombus resolution. The balance between uPA and PAI-2 could determine the fibrinolytic activity of the monocyte. Inhibiting PAI-2 production using specific antisense sequences might alter this balance. Selecting effective sequences is a problem as prediction of the secondary structure of target mRNA is difficult. This study reports the modification of a cell free system for rapid antisense screening.Five 18-19 mer oligodeoxynucleotides (ODN), sequences A, B, K, T and Q, and their matched scrambled controls were designed and screened using a modified rabbit reticulocyte lysate transcription and translation system (RRL). Intracellular uptake of ODNs was confirmed by fluorescence microscopy, scanning laser confocal microscopy and fluorimetery. Monocytes were transfected with a liposome/ODN complex using sequences A, B, A + B combined, or T and PAI-2 levels measured by ELISA. Inhibition of PAI-2 production was calculated as a percentage of control levels (baseline and scrambled).(i) RRL System – Sequence A was the most effective inhibitor of PAI-2 production in this system (median 63%) compared with sequences, B median 9%, K median 14%, T median 11% and Q median –8% respectively (n = 3). Sequence A was the only sequence, which always inhibited PAI-2. This was confirmed using fluorescently labelled protein (n = 2). (ii) Monocyte transfection Fluorescence microscopy and fluorimetry showed that intracellular delivery of labelled antisense was only achieved when a liposome was used. Transfection of monocytes extracted from 5 subjects showed that sequence A significantly reduced PAI-2 production (mean % 41.4, sem 9.1) compared with sequences B (mean% 3.4, sem 8.9, p = 0.04), A + B (mean % 0.4, sem 7.8, p = 0.04), and T (mean % 5.4, sem 4.9, p = 0.01). Futher studies using sequence A on cells from 10 subjects showed a significant reduction in monocyte PAI-2 production (27.6 ng/ml, sem 3.9) compared with matched scrambled controls (mean 38.3 ng/ml, sem 4.5, p = 0.0112) and baseline (mean 51.4 ng/ml, sem 6.7, p = 0.0009).Use of the RRL screening system allowed the selection of a novel antisense sequence, which significantly reduced PAI-2 production in monocytes.
Keywords: Plasminogen activator inhibitor–2 (PAI-2); antisense oligodeoxynucleotides; monocyte